2013
DOI: 10.1007/s12630-013-0080-y
|View full text |Cite
|
Sign up to set email alerts
|

Benzydamine hydrochloride on postoperative sore throat: a meta-analysis of randomized controlled trials

Abstract: Our results indicate that the incidence of POST can be significantly reduced by prophylactic BH topical application to the oral cavity or airway devices. Further RCTs are required to overcome the limitations of heterogeneity and to determine the optimal dosage and application of BH for managing POST.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…[ 17 ] Lignocaine spray decreased incidence of cough at tracheal extubation in surgeries of <2 h.[ 19 ] Medicated lozenges of licorice had efficacy of decreasing POST in smokers for surgery under GA of more than 1 h.[ 20 ] Recently, siccoral and strefen have been found to be effective in relieving POST in the early hours following extubation. [ 21 ] A meta-analysis found that the topical application of BH reduced the incidence of POST in patients following GA.[ 22 ] However, dipping of whole ETT cuff with benzydamine hydrochloride (BH) prior to anaesthesia induction had no influence on the incidence and severity of POST during 24 h post-operatively. [ 23 ] IV dexamethasone significantly reduced the risk and severity of POST at 24 h in a meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 ] Lignocaine spray decreased incidence of cough at tracheal extubation in surgeries of <2 h.[ 19 ] Medicated lozenges of licorice had efficacy of decreasing POST in smokers for surgery under GA of more than 1 h.[ 20 ] Recently, siccoral and strefen have been found to be effective in relieving POST in the early hours following extubation. [ 21 ] A meta-analysis found that the topical application of BH reduced the incidence of POST in patients following GA.[ 22 ] However, dipping of whole ETT cuff with benzydamine hydrochloride (BH) prior to anaesthesia induction had no influence on the incidence and severity of POST during 24 h post-operatively. [ 23 ] IV dexamethasone significantly reduced the risk and severity of POST at 24 h in a meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The NSAID most commonly investigated is benzydamine hydrochloride, a topical preparation that also has antibacterial properties. A meta‐analysis of benzydamine identified five randomised controlled trials that included 824 patients, one of which used supraglottic airway devices . For the studies investigating tracheal tubes, benzyamine was sprayed directly onto the tracheal tube and/or into the oropharynx in three studies while the remaining study used a benzyamine gargle.…”
Section: Methodsmentioning
confidence: 99%
“…Smaller tube size [5][6][7] Use of i-gel [50,[63][64][65] SAD rather than tracheal tube [121,122] Video laryngoscopy [9,10] 90°rotational insertion technique, use of introducing stylet for ProSeal LMA laryngeal mask [81][82][83][84][85] Oral rather than nasotracheal intubation [124] Limiting cuff pressure [32][33][34] Cuff pressure limitation ≤ 60 cmH 2 O [88][89][90][91][92][93]96] Cuffed rather than uncuffed tubes [125] Intravenous, topical or inhaled steroids [22][23][24][25] Topical steroids, NSAIDs, tramadol [98,101,102] Limiting tracheal tube cuff pressure [126] Topical NSAIDs [27][28][29]31] Propofol induction and maintenance [106,107] SAD cuff pressure limitation ≤ 60 cmH 2 O [130][131][132][133] Liquorice, magnesium and ketami...…”
Section: Tracheal Intubation Sads Childrenmentioning
confidence: 99%
“…Topical benzydamine hydrochloride. [ 10 ] intracuff[ 11 ] and topical lidocaine,[ 12 ] magnesium sulfate gargle,[ 13 14 ] nebulisations of ketamine and magnesium sulfate[ 15 ] are few examples.…”
Section: Discussionmentioning
confidence: 99%